Determinants of effective demand for public rental housing a case study of low-income and poor households in Valenzuela City, Metro Manila - Delas Nieves, John Paulo G.; Magnaye, Dina C. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
This thesis investigates the effective demand for rental housing among low-income and poor households in Valenzuela City, Philippines. The study aims to identify socio-economic factors influencing the decision to rent and the willingness to pay for public rental housing, using data collected from a household survey of 307 respondents across five selected barangays. Through a combination of descriptive statistics and regression analysis, the research provides insights into the demographic, financial, and housing characteristics of the target population. However, a key limitation identified in the study is the use of Disiplina Village as a model for rental housing. While Disiplina Village provides a useful reference, its unique characteristics, including the substantial investment of the national government, may not be fully generalizable to other contexts within Valenzuela City or similar urban settings.

The results indicated a near-universal willingness among the respondents to transition to public rental housing. The study found that the willingness to pay was generally feasible among both poor and low-income households, highlighting the potential for public rental housing to provide stable and affordable housing solutions. The projected monthly savings further underscored the potential financial relief for these households.

Regression analysis identified several key factors influencing this willingness to pay. Larger family sizes were found to decrease willingness to pay due to competing financial demands. In contrast, households with more working members or elderly dependents showed a higher willingness to pay, as additional income from these members increased financial capacity. Higher income of the household head was directly linked to greater affordability and willingness to pay for rental housing. Moreover, higher utility expenses often indicated a larger or more resource-intensive dwelling, correlating with a higher willingness to pay. Convenient access to workplaces, reflected in transportation expenses, increased the value placed on rental housing, thus enhancing willingness to pay. Additionally, larger floor areas were generally considered more desirable and commanded higher rental prices,

The discussion highlights the importance of designing public rental housing programs that cater to the specific needs of low-income and poor households. The study offers practical recommendations to enhance the effectiveness of rental housing programs in the Philippines. It suggests that policymakers should consider these socio-economic and demographic factors when designing public rental housing projects to better meet the needs of low-income and poor households. The research concludes by recommending continued government support and innovative funding mechanisms to sustain and expand rental housing initiatives in Valenzuela City. By doing so, the study aims to contribute to the development of more inclusive and sustainable public rental housing in Valenzuela City and beyond.
Keywords: Rental housing -- Philippines -- Valenzuela City; Housing -- Philippines -- Valenzuela City; Households -- Philippines -- Valenzuela City